Characterization of elderly and non-elderly patients with bronchial asthma - Pascoal, Adriana dos Santos (2016)
Background: It is clear that health literacy, namely having knowledge about one’s own disease (self-knowledge of the disease) and its management, is fundamental for reducing the impact of bronchial asthma, namely in terms of a patient’s asthma control and quality of life. Thus, the aims of the present study were to analyze the relevance and gaps of self-knowledge about asthma in the asthmatic patient; to evaluate whether having asthma affects the level of self-knowledge of the disease and which factors may be associated with poorer selfknowledge about asthma and, finally, whether this is different in the elderly versus younger asthmatic patients. Methods: Cross-sectional assessment of 92 elderly and 100 non-elderly asthmatic patients followed at Centro Hospitalar Cova da Beira, Portugal, with a control group of 100 elderly and 100 non-elderly non asthmatic patients. All volunteers signed a written informed consent form. Standardized and validated questionnaires were applied in order to evaluate depression, cognitive state, asthma control, quality of life, knowledge about the disease, and inhaler technique demonstration was also requested. Results were analysed using the Software Package for Social Sciences®, version 23.0. Results: All four groups had a clear predominance of women. Most elderly asthmatics and non-elderly asthmatics had no depressive humor on the GDS and on the CES-D, respectively. The majority had adult-onset / late-onset (AOA/LOA) asthma. Elderly asthmatic were mostly non-atopic whereas non-elderly asthmatics were preferentially atopic. More than two thirds had their asthma controlled in the past month, as assessed by ACT. Asthmatic patients significantly demonstrated a better knowledge level than non-asthmatic volunteers. Elderly Asthmatics had similar scores to those obtained by Non-Elderly Asthmatics for all four topics of the questionnaire. The elderly asthmatic patients with no depressive mood had a significantly higher level of self-knowledge than elderly asthmatic patients with depressive mood. Conclusions: We have confirmed that elderly asthmatic patients who are preferentially female, non-atopic, have LOA/AOA and are regularly follow up at specialty clinics can demonstrate similar results in self-knowledge score to those in non-elderly asthmatics. We also showed that depression is a significant negative factor influencing self-knowledge score in elderly asthmatic patients.